Between Liberal Aspirations and Market Forces: Obamacare's Precarious Balancing Act. Issue 4 (December 2014) - Oberlander, Jonathan
<x xml:space="preserve">Abstract</x> The 2010 Affordable Care Act (ACA) represents a milestone in U.S. health care policy. The ACA moves the American health care system away, in important respects, from market‐driven health care, including imposing new regulations on health insurers. Yet the ACA also relies, in other respects, on market forces to achieve its aims, including its embrace of health plan competition and high‐deductible insurance. This article explores how the ACA balances liberal aspirations and market principles, and the implications for health reform implementation and the future of U.S. health care.